RISK FACTORS OF SYNCOPAL STATE IN PEDIATRIC PATIENTS WITH LONG_TERM EFFECTS OF PERINATAL LESION OF CENTRAL NERVOUS SYSTEM - V.M. Shaitor; I. Yu. Mel'nikova; A.I. Safronova ("Paediatrician" Publishers LLC, 2008)
Complex clinical and neurophysiologic examination of 102 children (age 4-16 years) with verterobasilar insufficiency as a result of perinital lesion of central nervous system (CNS) was provided in this trial. 25% of patients (n = 25) had syncopal state (SS). Criteria of exclusion of pediatric patients from trial were rough organic CNS disorders, somatogenic and cardiogenic SS. Risk factors of SS were: Initially low bioelectric activity and decrease of compensatory function of cerebral cortex, initial and loading pulse volume deficit in verterobasilar pool, stenosis of vertebral arteries with decrease of blood velocity during functional tests, omegametry and stange's test data.Key words: children, perinatal lesion of central nervous system, syncopal state, risk factors.